Raft. - Goldenberg, Howard; Hybrid Publishers (Murrumbeena, Victoria : Hybrid Publishers, 2011)
Every year for over a decade Goldenberg, a white middle-aged doctor, has spent numerous periods working as a relieving doctor for Aboriginal communities in remote places. On these visits he has observed and recorded Aboriginal Australians lives without resorting to simplification or glib solutions. Among his true stories we meet psychotic Elijah who believes he is Satan's boss and cannot die; a dehydrated baby whose mother gambles away money for food; an old lady who receives a gashed head while fending off a thief stealing her money - her husband. In the midst of tragedy, suffering and moral ambiguity, these stories also tell of cultural richness and common humanity. Goldenberg writes: 'Aboriginal Australians are not at peace. They are variously unwell, underfed, overfed, afflicted excessively by our lifestyle diseases, confused by our drugs and drink, endowed with income but not with work, living in sickening poverty in paradisiacal places; and distracted from their serious cultural business by the trappings of our serious cultural emptiness.'.
General
Keywords: Biography & Autobiography - Personal Memoirs; Memoirs; Electronic books